Hypertensive disorders in pregnancy and timing of pubertal development in daughters and sons. Issue 9 (7th August 2020) - Lunddorf, Lea Lykke Harrits; Brix, Nis; Ernst, Andreas; Arendt, Linn H; Støvring, Henrik; Clemmensen, Pernille J; Olsen, Jørn; Ramlau-Hansen, Cecilia H
Abstract: STUDY QUESTION: Do maternal hypertensive disorders affect pubertal development in daughters and sons? SUMMARY ANSWER: Pubertal development tended to occur earlier in daughters of mothers with 'preeclampsia, eclampsia or HELLP syndrome' (hemolysis, elevated liver enzymes and low blood platelets) or hypertension in pregnancy compared to daughters born of normotensive mothers. WHAT IS KNOWN ALREADY: The existing literature suggests some or no association between preeclampsia and pubertal development in daughters, but not in sons. None of the previous studies has investigated the possible association between other types of hypertensive disorders (hypertension, eclampsia or HELLP syndrome) and pubertal timing in children. STUDY DESIGN, SIZE, DURATION: Longitudinal cohort study consisting of 15 819 mother–child pairs with information on maternal hypertensive disorders collected during pregnancy and information on pubertal development collected half-yearly from the age of 11 years and until fully developed or 18 years of age. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants are children from the Puberty Cohort nested within the Danish National Birth Cohort. The exposure was register-based and self-reported information on maternal hypertensive disorders during pregnancy. The outcomes were children's self-reported information on pubertal development, including Tanner stage 1–5 (pubic hair (both daughters and sons) and breast development (daughters) or genital development (sons)), first menstrual bleeding (daughters) or first ejaculation (sons), voice break episode (sons), axillary hair development and acne occurrence (both daughters and sons). The main outcome was mean difference in age at attaining each pubertal milestone and a combined pubertal marker in children of mothers with hypertensive disorders in pregnancy (either hypertension (n = 490), 'preeclampsia, eclampsia or HELLP syndrome' (n = 419) or 'unspecific hypertensive disorders' (n = 334) with unexposed children as reference (n = 14 576)). MAIN RESULTS AND THE ROLE OF CHANCE: In daughters of mothers with 'preeclampsia, eclampsia or HELLP syndrome', we observed tendencies of earlier pubertal timing (combined marker: −2.0 (95% CI: −3.9; 0.0) months). In daughters of mothers with hypertension, several pubertal milestones tended to occur earlier than in daughters of normotensive mothers; however, all 95% CIs overlapped the null resulting in a combined pubertal marker of −1.0 (95% CI: −3.2; 1.1) months. In sons of mothers with any of the hypertensive disorders, we observed no difference in pubertal timing (combined markers: 'preeclampsia, eclampsia or HELLP syndrome': 0.1 (95% CI: −2.0; 2.1) months; hypertension: −0.6 (95% CI: −2.3; 1.1) months; 'unspecific hypertensive disorders': 0.2 (95% CI: −1.9; 2.2) months). LIMITATIONS, REASONS FOR CAUTION: The study is subject to non-differential misclassification of self-reported information on maternal hypertensive disorders in pregnancy and current pubertal status; possibly causing bias toward the null. WIDER IMPLICATIONS OF THE FINDINGS: Hypertensive disorders in pregnancy might accelerate pubertal timing in daughters; however, more studies are needed for causal conclusions. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by the Faculty of Health at Aarhus University. The authors have no financial relationships or competing interests to disclose. TRIAL REGISTRATION NUMBER: N/A.